2023
DOI: 10.1186/s10020-023-00623-8
|View full text |Cite
|
Sign up to set email alerts
|

BMP7 ameliorates intervertebral disc degeneration in type 1 diabetic rats by inhibiting pyroptosis of nucleus pulposus cells and NLRP3 inflammasome activity

Abstract: Background Accumulating evidence indicates that intervertebral disc degeneration (IDD) is associated with diabetes mellitus (DM), while the underlying mechanisms still remain elusive. Herein, the current study sought to explore the potential molecular mechanism of IDD in diabetic rats based on transcriptome sequencing data. Methods Streptozotocin (STZ)-induced diabetes mellitus type 1 (T1DM) rats were used to obtain the nucleus pulposus tissues for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…The results showed that BMP7 could be used as a core gene, and NLRP3 inflammasome and pyroptosis related markers were significantly increased in NP cells. Further experimental detection showed that BMP7 inhibits the activation of NLRP3 inflammasome and cell pyroptosis processes, thereby slowing down the IDD of T1D rats ( 55 ). In addition, in T1D mice, higher levels of ADAMTS were shown in the intervertebral disc matrix, which mediated glycan fragmentation and IVD apoptosis ( 56 ).…”
Section: Abnormal Glucose Metabolism and Iddmentioning
confidence: 99%
“…The results showed that BMP7 could be used as a core gene, and NLRP3 inflammasome and pyroptosis related markers were significantly increased in NP cells. Further experimental detection showed that BMP7 inhibits the activation of NLRP3 inflammasome and cell pyroptosis processes, thereby slowing down the IDD of T1D rats ( 55 ). In addition, in T1D mice, higher levels of ADAMTS were shown in the intervertebral disc matrix, which mediated glycan fragmentation and IVD apoptosis ( 56 ).…”
Section: Abnormal Glucose Metabolism and Iddmentioning
confidence: 99%
“…Diabetes mellitus has been implicated as an indicator/contributor to IVDD. To understand diabetes mellitus type 1 (T1DM) induced IVDD, Yu et al confirmed IVDD in streptozotocin (STZ)-induced T1DM rats and performed NP transcriptome analysis in conjunction with microarray screening to identify genes relevant to IVDD in the T1DM rats [ 123 ]. This resulted in 35 potential genes of interest which were enriched in ECM, cytokine adhesion binding, and displayed prominent molecular function in apoptosis regulation and morphogenesis [ 123 ].…”
Section: Insights From Different Speciesmentioning
confidence: 99%
“…To understand diabetes mellitus type 1 (T1DM) induced IVDD, Yu et al confirmed IVDD in streptozotocin (STZ)-induced T1DM rats and performed NP transcriptome analysis in conjunction with microarray screening to identify genes relevant to IVDD in the T1DM rats [ 123 ]. This resulted in 35 potential genes of interest which were enriched in ECM, cytokine adhesion binding, and displayed prominent molecular function in apoptosis regulation and morphogenesis [ 123 ]. Interaction analysis of the 35 top differentially expressed genes (DEG) revealed Bmp7 , Ripk4 , Wnt4 , Timp1 , Col11a1 , Acp5 , V dr , Col8a1 , Aldh1a1 , and Thbs4 as the ten core genes in IVDD in STZ induced T1DM rats in descending enrichment [ 123 ].…”
Section: Insights From Different Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“… [ 49 ] HFD-fed, Fat-1 transgenic mice NLRP3 Increased HFD-induced expression of NLRP3, production of IL-1β and IL-18, and increased activity of caspase-1 in adipose tissue [ 50 ] HFD-fed, or STZ-induced diabetic Sprague–Dawley rats NLRP3 Increased expression of NLRP3 inflammasome components (NLRP3, ASC, caspase-1, IL-1β), NF-kB, and Nrf2 in liver [ 51 ] T1D Blood mononuclear cells (PBMCs) from T1DM patients NLRP1, NLRP3 Lower NLRP1, NLRP3, caspase-1 and IL-1β expressions. [ 52 ] STZ-induced T1DM rat NLRP3 Increased NLRP3, IL-18, IL1β and GSDM-D protein levels in nucleus pulposus tissues [ 53 ] NAFLD Liver and primary hepatocyte from HFD-fed mice NLRP3 Increased expressions of NLRP3, ASC, caspase-1, and increased caspase-1 activity and IL-1β level [ 54 ] Visceral adipose tissue from NAFLD/NASH patients NLRP4, NLRP6 Downregulated NLRP4, IL-1β, and upregulated NLRP6 expression in visceral adipose tissue, and increased circulating IL-18 levels in patients with pericellular fibrosis. [ 55 ] Liver samples from NAFLD patients, and ob/ob or Nlrp2 −/− mice NLRP2 Decreased mRNA and protein expression of Nlrp2 in NAFLD patient, and Nlrp2 −/− enhanced HFD-induced metabolic syndrome and insulin resistance.…”
Section: Nlrs In Cardiometabolic Diseasesmentioning
confidence: 99%